Desenvolvimento, caracterização e quantificação de nanopartículas de hidroxiapatita de cálcio associada à luteolina - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Aging results in the accumulation of molecular and cellular damage over time. To prevent and to retard the aging process, we use neocollagenesis mechanisms using collagen biostimulators, like hydroxyapatite (HAp), which is a calcium phosphate that triggers a controlled inflammatory response leading to the stimulation of fibroblasts to produce collagen. Another possibility is to use antioxidants (AO) to inhibit the reactions caused by reactive oxygen species (ROS) and free radicals, such as luteolin (LUT), a flavone from the flavonoid class, whose activity is attributed to the phenolic radicals in its chemical structure. The aim of this study was to develop, characterize and quantify calcium hydroxyapatite nanoparticles associated with LUT for potential use as a dermal biostimulator. HAp nanoparticles (n-HAp) were synthesized using the precipitation method. The n-HAp was used to obtain the composites, adding LUT and 99.5% ethyl alcohol in a SpeedMixer® and dried in a dry oven at 35oC for 48 hours. An analytical method in high performance liquid chromatography (HPLC) was developed and validated to quantify the incorporation efficiency of composites. The characterization of HAp-LUT composites, morphological and surface analysis was carried out, evaluating the average diameter, polydispersity index (IPD) and zeta potential by photon correlation spectroscopy, scanning electron microscopy (SEM-FEG), X-ray diffraction (XRD), spectroscopy via Fourier transform infrared spectroscopy (FTIR) and thermal spectroscopy via thermogravimetry (TGA). The composites were successfully synthesized using the proposed method. The analytical method developed was adequately validated, and the incorporation efficiency evaluation showed an incorporation efficiency of 81.50 and 95.46% for the HAp-LUT composites. The physical-chemical analyses showed an average diameter of 263.4 to 846.5 nm, IPD of 0.613 to 0.884, and zeta potential of -31.5 to -5.18 mV, indicating that the composites are heterogeneously distributed and have low electrical stability, resulting in the formation of agglomerates of micrometer-sized nanoparticles. Morphological and surface analysis showed the composites to have an irregular shape and roughness, and elongated structures with a smooth surface. XRD analysis showed a reduction in crystallinity peaks with consequent amorphization of the drug. Structural analysis by IVTF confirmed that there was no chemical reaction between LUT and HAp, indicating that HAp can serve as a carrier for LUT without interfering with its release. TGA showed an improvement in the thermal stability of the composites. Thus, it is concluded that the HAp-LUT composite was successfully developed and presented suitable physicochemical characteristics for use as a potential collagen biostimulator. Further stability and cytotoxicity tests are still needed to guarantee its safety and efficacy.
Keywords: antioxidante; bioestimulador dérmico; colágeno; flavona; rejuvenescimento; anti-aging; antioxidant; collagen; dermal biostimulator; flavone; CNPQ::CIENCIAS DA SAUDE